Urban and Regional Policy and its Effects, 2. - Pindus, Nancy (Brookings Institution Press, 2009)
The goal of this book, the second in a series, is to inform policymakers, practitioners, and scholars about the effectiveness of select policy approaches, reforms, and experiments in addressing key social and economic problems facing cities, suburbs, and metropolitan areas. What can we say about what works, what doesn't, and why? And what does this knowledge and experience imply for future policy questions?The authors take a fresh look at several different issues (e.g., education, economic development, land use) and conceptualize how each should be thought of. Once the contributors have presen.